Soil–landform Relationship and Pedogenesis of Flood Plain Soils of Mahananda Sub-basin, Bihar - S.K. Reza (Journal of the Indian Society of Soil Science, 2022)
Alluvial flood plain soils are one of the major soil groups in northern Bihar and are highly heterogeneous as a result of the hydromorphic environment in which they are formed. Hence, the present investigation was carried out to understand the soil-landform relationship in Katihar district of Bihar. Five major landforms like old alluvial plains (1.97%), young alluvial plains (35.64%), meander plains (30.85%), flood plains (25.35%) and, char land and point (4.5%) were identified after visual interpretation of Sentinel-2 data in conjunction with survey of India toposheet and digital elevation model (SRT DEM). The detailed soil survey was carried out to understand the variability in the study area and 200 soil profiles were studied in different identified landforms. The soils of active alluvial plain (flood plain, char land and point bar) showed wide range of soil morphological properties with lithological discontinuities. Low chroma and value in soils of meander plain due to poor drainage conditions and high groundwater table showed gleying characteristics. The soils of young alluvial plain and active alluvial plain showed irregular distribution of clay content, cation exchange capacity (CEC) and organic carbon (OC). This study indicates that the soillandform relationship in alluvial floodplains of Mahananda sub-basin partially followed due to mass movement of sediments from Himalayas, periodic flooding and deposition of alluvium during different fluvial cycles of Mahananda river and its tributaries. This was further confirmed by study on pedogenic indices of different landforms. The study on pedogenic indices in two selected sites (window area) away from the Mahananda river like fine sand/total sand, very fine sand/total sand, sand/silt, silt/clay, index of weathering and CEC/clay in the study area doesn’t follow the trend in the flood plain as compared to nearly stable land. This may be due to the effect of shifting of river course and their tributaries in the selected two window areas across the different landforms. To overcome the above mentioned problems in soil-landform relationship in the study area, the identified landforms were further sub-divided based on the local factors like percentage of crop cover and moisture content. In revised landforms soil types present in each landform showed soil-landform relationship. Thus, the knowledge on soils in relation to landforms vis-à-vis soil properties and their pedogenesis is useful in understanding their potentials and problems for sustainable land use planning.